Pengaruh Pembelajaran Sosial Emosional Versus Konvensional dan Motivasi terhadap Hasil Belajar Mapel Kimia Siswa Kelas X di SMA Negeri 20 Surabaya - Pamungkas, Agus Dwi; Rusmawati, Retno Danu; Harwanto, Harwanto (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
The development of this research was carried out with the aim of finding answers to the problems described in the problem formulation above, namely to find out differences in learning outcomes in students who took Social Emotional Learning (PSE) versus conventional in chemistry subject class X at SMA Negeri 20 Surabaya, to find out differences in learning outcomes for students who have high and low learning motivation in chemistry subject class XI at SMA Negeri 20 Surabaya, to determine the interaction between Social Emotional Learning (PSE) and motivation on learning outcomes at SMA Negeri 20 Surabaya. In this study, the population used was a limited population and the sample in this study was 114. The data analysis technique used in this study was two-way analysis of variance. used to test the hypothesis, the hypothesis can be accepted and tested for truth if the price of the F table is greater than the probability value, with a significant level of 0.05. Data collection methods used in this research are questionnaires and tests. The design used in this research is a 2x2 factorial design. Based on the data obtained in this study it can be concluded that Social Emotional Learning (PSE) and Conventional Learning have an influence on student learning outcomes, this can be seen from the t test. There is a significant difference between the two methods as indicated by a significant difference in the t value between the two methods, where the PSE t value is greater than the conventional learning t value. It can be said that Social Emotional Learning has more influence on learning outcomes compared to Conventional Learning. In other words, the first hypothesis that there is a difference between the two methods is acceptable. There are differences in learning outcomes between students who have high learning motivation compared to students who have low motivation. This can be seen from the t test of learning motivation on learning outcomes with a significance value below 0.05, which means that the second hypothesis is accepted.